Pilot error and its relationship with higher organizational levels: HFACS analysis of 523 accidents - Li, Wen-Chin; Harris, Don (Aerospace Medical Association, 2006)
Introduction: Based on Reason’s model of human error, the Human Factors Analysis and Classification System (HFACS) was developed as an analytical framework for the investigation of the role of human error in aviation accidents. However, there is little empirical work that formally describes numerically the relationship between the levels and components in the model (the organizational structures, psychological pre-cursors of errors, and actual errors). Method: This research analyzed 523 accidents in the Republic of China (ROC) Air Force between 1978 and 2002 through the application of the HFACS framework. Results: The results revealed several key relationships between errors at the operational level and organizational inadequacies at both the immediately adjacent level (preconditions for unsafe acts) and higher levels in the organization (unsafe supervision and organizational influences). Conclusions: This research lends support to Reason’s model that suggests that active failures are promoted by latent conditions in the organization. Fallible decisions in upper command levels were found to directly affect supervisory practices, thereby creating preconditions for unsafe acts, and hence indirectly impaired performance of pilots, leading to accidents. The HFACS framework was proven to be a useful tool for guiding accident investigations and developing accident prevention strategies.
Keywords: accident investigation; human error; Human Factors Analysis and Classification System; HFACS